Traditional Oral Remedies and Perceived Breast Milk Insufficiency Are Major Barriers to Exclusive Breastfeeding in Rural Zimbabwe. Issue 7 (14th May 2014) - Desai, Amy; Mbuya, Mduduzi N.N.; Chigumira, Ancikaria; Chasekwa, Bernard; Humphrey, Jean H.; Moulton, Lawrence H.; Pelto, Gretel; Gerema, Grace; Stoltzfus, Rebecca J.; ,
Abstract: Only 5.8% of Zimbabwean infants are exclusively breastfed for the first 6 mo of life despite substantial investment in exclusive breastfeeding (EBF) promotion throughout the country. We conducted a survey of 295 mothers of infants <6 mo of age who were recruited from rural immunization clinics and outreach sites in the Midlands Province of Zimbabwe. We explored infant feeding knowledge, beliefs and attitudes, and details regarding facilitators for EBF mothers and first foods fed by non-EBF mothers to identify and understand barriers to EBF. Among mothers of infants <1 mo, 1 to <2 mo, and 2–6 mo of age, 54%, 30%, and 12%, respectively, were practicing EBF. In adjusted multivariate analyses, EBF practice was positively associated with belief in the sufficiency of EBF ( P = 0.05), belief in the avoidance of cooking oil feeding (a common traditional practice) in the first 6 mo ( P = 0.001), and perceived pressure from others regarding infant feeding and traditional medicine use ( P = 0.03). Psychosocial support and viewing breast milk as sufficient were reported as primary facilitators of EBF practice. Maternal responses to open-ended questions identified protection, nutrition, and crying as the main reasons for EBF interruption. During the first 2 mo of life, "protection feedings" using traditional oral remedies (such as cooking oil and water) to prevent or treat perceived illness, specifically colic and sunken/depressed fontanel, made up 78.5% of the non-breast milk feeds. From the second month of life, "nutrition feedings, " mainly of water and porridge, were given when mothers believed their breast milk was insufficient in quantity or quality to meet the hunger or thirst needs of their infants. Our findings underscore the importance of exploring cultural beliefs and practices as they pertain to infant feeding and care and present insights for designing and targeting EBF promotion interventions.